General Aviation in Iran - Challenges and Opportunities - Mohammadi-Amin, Meysam; Karimi, Nima (International Journal of Engineering and Technology, 2018)
One of the development indicators in different countries is the development of the transportation infrastructure. Aviation, as one of the transportation networks, plays an important role in the economic, social and cultural development of every countries. In this paper, Iran Aviation Network has been studied and reviewed based on domestic flight parameters such as flight frequencies of airport and the average number of passengers per flight. It is concluded that Iran's Aviation Network does not have a uniform dispersion of traffic and this lack of uniformity can be seen in the ineffectiveness of some airports and the load factor in some regional flights. This problem can be handle using general aviation aircrafts. The use of airplanes with less passenger capacity will increase the flight frequency and load factor. So, increasing these two parameters will increase profit, especially in small airports and short routes. This process can balance the air transport network cycle in Iran and increase its efficiency and uniformity.Â Â